Stakeholder Pressure, Environmental Strategies, and Hotel Performance: The Role of Environmental Management Accounting - Utama, I Made Karya; Suryanawa, I Ketut; Antari, Ni Wayan Meli; Widiantara , I Komang (Jurnal Ilmiah Akuntansi dan Humanika, 2024)
The objective of this research is to investigate the role of stakeholders' pressure, environmental strategies, and environmental management accounting (EMA) on the company's competitive advantage of the hotel industry. The research on the issue of environmentally friendly business activities, in this case, the company's strategies related to green activities, particularly the implementation of environmental management accounting (EMA) in the hotel industry, is important because hotels are one of the supporting facilities for tourism that involve humans, living beings, and the environment. Data analysis was conducted by using Multiple Linear Regression by the SPSS (Statistical Package for the Social Sciences) version 24 application. The analysis results show: Stakeholder pressure does not affect competitive advantage, Environmental strategy positively affects competitive advantage, Implementation of environmental management accounting (EMA) positively affects competitive advantage.